A rare case of recurrent hypoglycaemia - Goswami, Sourabh; Meena, Priyanka; Keswani, Prakash; Sharma, Ramji (International Journal of Research in Medical Sciences, 2020)
Very often clinicians are confronted with unconscious patients; the cause being hypoglycaemia. In addition to correction of hypoglycaemia promptly, a search for the cause of hypoglycaemia must be attempted at the earliest with a stepwise approach. Here, the authors present a rare case of recurrent hypoglycaemia where a stepwise approach ultimately led to a diagnosis, but there were various reports which were misleading. The diagnosis was insulinoma which was apparent from the history and presenting features. But, the initial investigations, even though having high sensitivity, were normal, thus leading to a more invasive approach. The patient was ultimately cured by enucleation.